Humanism and Protestantism in early modern English education - Green, I. M. (St Andrews studies in Reformation history, 2009)
This volume is the first attempt to assess the impact of both humanism and Protestantism on the education offered to a wide range of adolescents in the hundreds of grammar schools operating in England between the Reformation and the Enlightenment. By placing that education in the context of Lutheran, Calvinist and Jesuit education abroad, it offers an overview of the uses to which Latin and Greek were put in English schools, and identifies the strategies devised by clergy and laity in England for coping with the tensions between classical studies and Protestant doctrine. It also offers a reass